Potential of 5% tamarind extract gel as an etching agent: tensile strength and scanning electron microscope (SEM) evaluation - Erawati Wulandari; Faiqatin Cahya Ramadhani; Nadie Fatimatuzzahro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Acid etching is a stage in obtaining bonds between composites and enamel. The application of acid to the enamel surface, however, can cause dissolution of hydroxyapatite and demineralisation of the enamel surface. Phosphoric acid, a strong acid, is an etching material that can reduce enamel hardness. Excessively reducing hardness can interfere with attachment to the restorative material. One medicinal plant that can be used as an alternative material in acid etching is tamarind. Purpose: This study aims to determine the effect of 5% tamarind extract gel on the tensile strength of composite resins. Methods: This is an experimental research study with a post-test-only control-group design. The study used 14 mandibular incisors. The labial part of the incisor was prepared using a diamond fissure bur with a diameter of 4 mm and a depth of 2 mm. The control group was then etched with 37% phosphoric acid gel, while the experimental group was etched with 5% tamarind extract gel. Bonding resins and micro-hybrid composite resins were applied, based on the manufacturers’ instructions. Next, a tensile strength test and seeing formation resin tags by scanning electron microscope (SEM) were performed. Data were analysed using an independent t-test (p < 0.05). Results: The average tensile strength of composite resins in the group etched with 5% tamarind extract gel was the same as in the 37% phosphoric acid group (p > 0.05). SEM images also show that enamel etched with 5% tamarind extract gel produced a tag similar to that etched with 37% phosphoric acid gel. Conclusion: 5% tamarind extract as an etching material can generate tensile strength of composite resin and trigger formation of resin tags in the same way as 37% phosphoric acid.